Utilization of E-Books and Online Articles to Improve Students' Reading Skills - Dian Pratiwi; Medi Yansyah (Universitas Muhammadiyah Lampung, 2024)
This study explores the use of e-books and online articles to improve university students’ reading skills, particularly focusing on comprehension, reading frequency, and intrinsic motivation. Conducted through a Classroom Action Research (CAR) approach involving two intervention cycles, the study involved 24 students from the English Education Department at Universitas Muhammadiyah Pringsewu. Data were gathered via reading comprehension tests, questionnaires, and classroom observations to assess both cognitive and affective changes during the intervention. The results show notable improvements in students’ reading comprehension, as seen in the consistent rise in test scores from the pre-test to Cycle II. Furthermore, students exhibited greater reading interest, higher reading frequency, and a clear shift from lecturer-led to self-motivated learning. These findings suggest that digital reading materials serve as an effective and engaging tool for developing academic literacy, endorsing the inclusion of technology-based resources in higher education reading programmes.